STUDI DESKRIPTIF PENERAPAN DISIPLIN POSITIF PADA PESERTA DIDIK - Rahmad, S.Pd; Rahmat Putra Yudha (JARDIKNAS - Jurnal Pendidikan dan Sosial, 2020)
Analysis of the application of Positive Discipline in the classroom for students is a new way to motivate students in learning. The granting of physical punishment or intimidation applied is a matter of old-fashioned way of educating and not having a positive impact. With the application of positive discipline, it is expected to have a better impact on students. The goal is to find out the form of the application of positive discipline, to know the interaction and oppose the application of positive discipline to students, and to find out the application of the positive discipline. Descriptive research method using literature study data collection. Results and conclusions of the analysis in the form of form theory and the application of positive discipline in the form of mutual respect for dignity, dignity, behavioral development, discipline and self-control, friendly character, active child participation, Respect the development and quality of life of children, Avoid motivation, find children about life, question honesty, equality, non-argument, solidarity and fairness. Inhibiting factors, habits, habits, the same punishment with love.